Pengaruh Perkembangan Teknologi Terhadap Etika Profesionalisme Advokat : Promosi Jabatan Melalui Media Sosial - Arif Hardiyanto; Sena Neranda; Adzan Dylan Caesarrio; Maman Dana Darmana; Ihsan Sanjaya (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The advancement of information technology and the widespread adoption of social media have significantly influenced the practice of the legal profession, particularly among advocates. While technology offers new avenues for disseminating legal knowledge and enhancing access to justice, it also introduces complex ethical challenges. This paper explores various ethical breaches committed by advocates via social media platforms, including excessive self-promotion, making guarantees of legal success to clients, and potential breaches of client confidentiality. Adopting a normative legal approach, this study examines the legal framework provided by Law No. 18 of 2003 on Advocates and the Indonesian Advocate Code of Ethics (KEAI), and highlights the persistent weaknesses in ethical oversight within professional advocate organizations. The findings underscore the urgent need to modernize supervisory mechanisms, develop ethical guidelines for digital conduct, and reinforce the role of professional bodies in educating and disciplining members. To preserve the dignity and integrity of the legal profession in the digital era, the use of technology by advocates must align with ethical principles, professional standards, and a commitment to public responsibility.